Comparison of Anatomical Structure of Maize (Zea mays L.) Plant of Gorontalo Local Variety Pulut and Momala - Ahaya, Cindi; Kandowangko, Novri Youla; Febriyanti, Febriyanti; Ahmad, Jusna; Pagalla, Devi Bunga (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2025)
One of the primary agricultural commodities that contributes significantly to global food security is maize (Zea mays L.), a monoecious cereal plant of the Poaceae family with distinct but identical male and female blooms. Local cultivars like Pulut and Momala in Gorontalo have exceptional promise that requires further study, particularly with regard to their anatomical makeup. This study Comparing the two types' stem and leaf anatomical features, including vascular tissue (xylem and phloem), epidermis, and stomata, is the goal of this study. A qualitative descriptive approach was used to make the observations, which were subsequently evaluated and shown as a comparison table. The results showed that at the age of 30 and 40 HST, the network of vessels (xylem and phloem) and epidermis on the stems and leaves of Pulut and Momala corn varieties reflected a development pattern that supported the transportation of water, minerals, and nutrients. The number of stomata in Pulut varieties decreased due to less than optimal growth, while Momala varieties showed an increase in the number of stomata which was influenced by the growth period with environmental conditions suitable for corn plants.